PENGARUH LOKASI DAN HARGA TERHADAP MINAT BELI DI RENAISSANCE BALI ULUWATU RESORT & SPA - Permata Brata, Ni Made Emmy Pasya; I Gusti Agung Gede Witarsana; Ni Made Suastini (Program Studi Administrasi Perhotelan, 2024)
The purpose of the study was to ascertain how price and location affected consumers' desire to purchase. The Renaissance Bali Uluwatu Resort & Spa served as the venue for this study. One hundred visitors who were familiar with the hotel but had never been there made up the study's population. Multiple linear regression is used in the analytical process using SPSS version 26 for Windows. The study's findings show that, with tcount > ttable = 4.591 > 1.660 and a significance value < ? = 0.000 < 0.05, the Location Variable (X1) partially and influences Buying Interest. At tcount > ttable value = 6.378 > 1.660 and significance value < ? = 0.000 < 0.05, the Price variable (X2) has a somewhat positive and significant influence on Purchase Intention. Simultaneously, the location and price variables affect the Buying Interest with values ??of Fcount > Ftable = 66.172 > 3.09 and significance < = 0.000 < 0.05. It can be inferred from the study's results that Location and Price have a positive and significant impact on Buying Interest and simultaneously have an impact on Buying Intention at Renaissance Bali Uluwatu Resort & Spa.